Harnessing Oncolytic Virus-mediated Anti-tumour Immunity - Lemay, Chantal (Université d'Ottawa / University of Ottawa, 2012)
Treatment of permissive tumours with the oncolytic virus (OV) VSV-Δ51 leads to a robust anti-tumour T cell response, which contributes to efficacy; however, many tumours are not permissive to in vivo treatment with VSV-Δ51. In an attempt to channel the immune stimulatory properties of VSV-Δ51 and broaden the scope of tumours that can be treated by an OV, a potent oncolytic vaccine platform was developed, consisting of tumour cells infected with VSV-Δ51. I demonstrate that prophylactic immunization with this infected cell vaccine (ICV) protected mice from subsequent tumour challenge, and expression of GM-CSF by the virus (VSVgm-ICV) increased efficacy. Immunization with VSVgm-ICV in the VSV-resistant B16-F10 model induced maturation of dendritic cells, natural killer (NK) cells, and T cells. I demonstrate that this approach is robust enough to control the growth of established and spontaneous tumours. This strategy is broadly applicable because of VSV’s extremely broad tropism, allowing nearly all cell types to be infected at high MOIs in vitro, where the virus replication kinetics outpace the cellular IFN response. It is also personalized to the unique tumour antigen(s) displayed by the cancer cell. Histone deacetylase inhibitors (HDIs) can augment viral replication, making them particularly interesting complements to OV therapy. However, the impact of HDIs on the generation and re-stimulation of immune responses remains to be clearly elucidated. Along with my collaborators at McMaster University, I demonstrate that MS-275, but not SAHA, selectively depletes naïve and regulatory lymphocytes. Memory lymphocytes that are being boosted remain unscathed and even have enhanced cytokine production, potentially as a consequence of the depleted lymphocyte compartment. This leads to a delay in anti-VSV neutralizing antibodies and T cell responses. Interestingly, HDI treatment of B16-F10 cells appears to inhibit VSV replication but allows for a longer persistence within the tumour. When used in an oncolytic prime/boost vaccination model, MS-275 potently enhanced survival. Though the anti-tumour immune response is enhanced, a near complete reduction in autoimmune vitiligo is observed with MS-275 administration. Therefore, this HDI uniquely modulates the immune response to enhance anti-tumour immunity and decrease the anti-viral response, while also decreasing autoimmune sequelae.
Keywords: Oncolytic Virus; Cancer; Immunotherapy; Vaccine